CARLOTA RAINHA, DE ROBERTO ATHAYDE: A HISTÓRIA PORTUGUESA NA DRAMATURGIA BRASILEIRA - DITTERT, MARIANA (2022)
The main objective of this thesis is to analyze the literary work “Carlota Rainha” (1998), by Roberto Athayde, a 20th-century play, whose theme deals with the beginning of democracy in 19th century Brazil, rescuing the Portuguese history and bringing it to our Brazilian dramaturgy. In particular, the figure of Carlota Joaquina, the protagonist of Athayde and, mainly, of the History of Brazil, recovering her image under new perspectives, since, until now, most materials about her consider her a wanton queen, as pointed out by João Felício dos Santos (2008), among many other scholars. We have selected Bertold Brecht's Epic Theater as the main contribution to the analysis since it is Brecht who establishes the basis of contemporary theater as a weapon of social criticism, a scenario in which the play, which serves as the corpus of our analysis, is inserted. In addition, we present a historical path, which permeates the story of Carlota Joaquina as queen of Portugal and Brazil, and a fictional plan, as a character created by Athayde; it was also pertinent for rescuing the history of Brazilian theater, establishing the complex scenario in which Brazilian dramaturgy permeated and had to resist as an art pursued over the years, to point out the strengthening and use of theater as a form of thinking about society critically.